Daya Terima Abon Ikan Rucah Tiga Waja sebagai Alternatif Pemberian Makanan Tambahan (PMT) Lokal Ibu Hamil KEK - Wijayanti, Anggi Ariana; Susiloretni, Kun Aristiati; Noviardhi, Astidio (JURNAL RISET GIZI, 2024)
Background : The prevalence of Chronic Energy Malnutrition (CEM) in pregnant mother in Indonesia is still high of 17,3%. Balanced energy-protein food supplementation is an effective intervention to improv nutritional status of pregnant mother. Fish has high protein content with good essential amino acid and minerals especially calcium, potassium, selenium, zinc, iodine and fluorine. So, the need for the development of fish processing product like tiga waja trash fish floss as food supplement for pregnant mother based local food. Objectives : This study aimed to give quantitative description of the nutritional composition of tiga waja trash fish floss, heavy metal content and sensory evaluation.Methods : This research is an experimental study with a repeated measure design. Sensory test data was collected by quota sampling on 15 trained panelists with hedonik quality testing and 25 moderately trained panelists with hedonik tests. Nutrional content analyzed included macro-micronutrients and heavy metal content test. Results : The macronutrients content of tiga waja trash fish floss (100 g) included 24,94% protein, 508,45 kcal, 30,25% fat, 33,11% carbohydrate. Calcium 908,86 mg/100g and  selenium 51,80 mcg/100g  content was indicated in high level. It's also containing good quantities composition of other nutrients such as zinc, omega 6 fatty acids, omega 3 fatty acids, PUFA, MUFA, and SFA. Tiga waja trash fish floss is safe for consumption, it’s no heavy metal contamination. The sensory evaluation of  hedonik test is an effect of spice variation treatment on color (p<0.05), but no effect of spice variation treatment on taste, aroma and texture (p>0.05) the average treatment is accepted in the like category and the most preferred is V4 (Soto). The hedonik quality test was no effect on the quality tiga waja trash fish floss (p>0.05).Conclusion : Tiga waja trash fish floss possessed good quantities of macronutrients, minerals, and unsaturated fat content. It’s can be treated as a  local food supplement for undernourished mothers, with adding other food ingredients to meet the caloric and carbohydrate values.